the Utilizing APOS Theory to Enhance Conceptual Understanding through Interactive E-Modules in Elementary Mathematics Learning - Ni Luh Made Puspita Sari; Gusti Ngurah Sastra Agustika; Agung Ayu Dewi Sutyaningsih (Thinking Skills and Creativity Journal, 2025)
The low learning outcomes in mathematics at SD Negeri 2 Abianbase are caused by reliance on textbooks and a lack of varied learning media, especially digital media. This leads to students struggling to understand the material and being less motivated to learn. This study aims to develop an E-Module based on APOS Theory to enhance the conceptual understanding of grade IV students. The development model used is ADDIE, which consists of analysis, design, development, implementation, and evaluation. The participants in this study were 20 grade IV students at SD Negeri 2 Abianbase. Data were collected through interviews, observations, and essay tests, with data analysis using descriptive quantitative, descriptive qualitative, and inferential statistical analysis. The results show that the APOS Theory-based E-Module is valid based on media expert validation and trials with students, receiving a very high score. This E-Module is proven to be effective in improving students' understanding, as evidenced by the improvement in test scores before and after using the E-Module. This research contributes to the development of digital learning media that can enhance student motivation and mathematics learning outcomes.